Nutrient Pollution and Predation Differentially Affect Innate Immune Pathways in the Coral Porites porites - Dougan, Katherine E.; Ladd, Mark C.; Fuchs, Corinne; Vega Thurber, Rebecca; Burkepile, Deron E.; Rodriguez-Lanetty, Mauricio (Frontiers in Marine Science, 2020)
Reef-building corals face a multitude of threats not only from global climate change but also local stressors such as nutrient pollution. Nutrient enrichment can amplify the negative effects of predation on corals by facilitating dysbiosis in the coral microbiome that leads to coral mortality. These patterns suggest that nutrient pollution might suppress the capacity of the coral immune system to respond to microbial infections that follow mechanical injury from predation. Here, we measured the impact of nutrient enrichment and predation on tyrosinase-type and laccase-type phenoloxidase (PO) activities, which are key components of immune defense pathway involved in melanin synthesis and wound healing in corals. Corals were exposed in situ to either ambient or enriched nutrient levels in combination with either no damage, mechanical damage, or predation damage from parrotfishes. The activity of PO enzymes in response to both tyrosinase-type substrates significantly decreased under nutrient enrichment, suggesting that corals became immune-compromised. Predation damage also increased laccase activity, implicating it in tissue repair and potentially defense from pathogens. Our findings highlight the need to mitigate nutrient pollution on coral reefs, as higher nutrient levels suppress important coral immune pathways and likely contribute to patterns of increased coral disease and subsequent mortality on reefs plagued by nutrient enrichment.